Human-centred requirements engineering - Gregoriades, Andreas; Shin, Jae Eun; Sutcliffe, Alistair G. (My University, 2004)
This paper describes the influence of human factors in the requirements engineering process of socio-technical systems design. In particular, we examine agents' workloads and the partitioning of system requirements into automated functions, collaborative task support or manual procedures. We assess workload in terms of communication and the task load that each agent is able to handle. We illustrate the application of the approach in complex socio-technical systems such as the command and control rooms of military vessels. A case study is presented that demonstrates the use of a tool, HUCRE (Human-Centred Requirements Engineering) that assesses workloads of agents and assists the diagnosis of potential system failure. A preliminary evaluation of the HUCRE method and tool is reported, demonstrating that requirements engineers can address human factors issues using the support tool.
Keywords: Automated functions; Human factors; Military vessels; Socio-technical systems